Women and Modern Families: An Analysis of Quraish Shihab's Perspectives - Wahyuni, Tuty (Jurnal Pemikiran Islam, 2024)
In modern families, Islamic values are increasingly eroded due to the challenges posed by the advancement of information and communication technology. In contemporary Muslim families, wives often work outside the home but still serve as the primary educators within the family. This article aims to elucidate the concept of a harmonious family in the context of modern life, according to Quraish Shihab. The research employs a qualitative method with data collection techniques based on a literature review, examining Quraish Shihab's thoughts through his works from 1996 to 2022, encompassing ten books related to family issues. The findings reveal that Quraish Shihab places significant emphasis on the role of women and family. According to his works, including "Perempuan" and "Pengantin Al-Qur’an," a harmonious family involves prospective spouses getting to know each other before marriage, having a lawful marriage contract in Islam, and ensuring the presence of a guardian during the marriage ceremony. Couples should support each other, exchange roles, and maintain good communication. Shihab also highlights the importance of women's roles in working and education in modern families, advocates for balanced marriage ages, and outlines the conditions under which divorce is permissible in Islam. These principles are highly relevant to the realities faced by modern families today.